Cryptogenic fibrosing alveolitis: prediction of fibrogenic activity from immunohistochemical studies of collagen types in lung biopsy specimens. - Bateman, E D (1983)
Collagen immunofluorescence studies were performed on biopsy specimens from 25 patients with cryptogenic fibrosing alveolitis. We studied the relationship of these results to the clinical, radiological, and physiological assessments of disease activity during six-month periods before and after the lung biopsy; to the appearances on routine histological examination; to the inflammatory cell proportions in bronchoalveolar lavage fluid; and to the response to treatment. Positive associations were observed between the presence of type III collagen and disease activity before (p less than 0.015) and after (p less than 0.02) lung biopsy. These were independent of clinical and routine histological features. The type-III-positive group also contained nine of the 11 responding to treatment. None of the type-III-positive patients had a quiescent or stable course. In contrast, most patients with no type-III-collagen fluorescence had a stable course over the time of this study and did not improve on treatment. It is suggested that collagen typing may be an additional useful method of assessing potentially reversible disease in cryptogenic fibrosing alveolitis.